Acquisition of a Joystick-Operated Video Task by Pigs (Sus scrofa) - Croney, Candace C.; Boysen, Sarah T. (Frontiers in Psychology, 2021)
The ability of 2 Panepinto micro pigs and 2 Yorkshire pigs (Sus scrofa) to acquire a joystick-operated video-game task was investigated. Subjects were trained to manipulate a joystick that controlled movement of a cursor displayed on a computer monitor. The pigs were required to move the cursor to make contact with 3-, 2-, or 1-walled targets randomly allocated for position on the monitor, and a reward was provided if the cursor collided with a target. The video-task acquisition involved conceptual understanding of the task, as well as skilled motor performance. Terminal performance revealed that all pigs were significantly above chance on first attempts to contact 1-walled targets (P < 0.05). These results indicate that, despite dexterity and visual constraints, pigs have the capacity to acquire a joystick-operated video-game task. Similar methodology may prove useful in future studies of the cognitive capacities of pigs and other domestic animals.